AJARAN KETUHANAN DALAM LONTAR BUBUKSAH - ecy wulandari12 (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
One of the religious texts whose text contains divine teachings is Lontar Bubuksah which specifically explains about Shiva Buddha. Bubuksah is an imaginative story script about a religious literary work, as a story with a religious breath expressing the ideals and essence of liberation of the soul towards a pure nature, namely Moksa, in the Bubuksah text it tends to be Guruistic which takes its source from the doctrine of Shiva (Bhatara Guru) as a god. highest. Gagakaking represents Shiva's doctrine while Bubuksah represents Buddhist doctrine. which Bubuksah as a representation of the Buddhist pedanda in Bali which comes from the teachings of Bhatara Guru (Guruistick sources). In the end Gagakaking and Bubuksah represented the revered priest Sewa Sogata as a manifestation of Bhatara Guru. This is what distinguishes it from other Buddhist teachingsKeywords: Divinity, Bubuksah